Final Report of the Farmworker Opportunity Project 1967 - American Friends Service Committee::::::; John Flynn::::::; Harold Kachigian::::::; Peter Lauwerys::::::; Christopher Paige::::::; Fred Roske::::::; Kirke Wilson:::::: (1967)
A report discussing the impact of the Farm Worker Opportunity Project on agricultural laborers and agriculture in California.